Fermented Soybean Meal Replacement in the Diet of Lactating Holstein Dairy Cows: Modulated Rumen Fermentation and Ruminal Microflora - Wang, Zuo; Yu, Yuannian; Li, Xinyao; Xiao, Hongyan; Zhang, Peihua; Shen, Weijun; Wan, Fachun; He, Jianhua; Tang, Shaoxun; Tan, Zhiliang; Wu, Duanqin; Yao, Hui (Frontiers in Microbiology, 2021)
This study was conducted to examine the influences of replacing soybean meal (SBM) with fermented soybean meal (FSBM) in the diet of lactating Holstein cattle on rumen fermentation and ruminal bacterial microbiome. Twenty-four lactating Chinese Holstein dairy cattle were assigned to each of the two treatments in a completely randomized design: the SBM group (the basal total mixed ration [TMR] diet containing 5.77 % SBM) and the FSBM group (the experimental TMR diet containing 5.55 % FSBM). This trial lasted for 54 days (14 days for adjustment and 40 days for data and sample collection), and samples of rumen liquid were collected on 34 d and 54 d, respectively. The results showed that replacing SBM with FSBM significantly increased the molar percentages of propionate (P < 0.01) and valerate (P < 0.05), but reduced the total volatile fatty acid (TVFA) concentration (P < 0.05), butyrate molar proportion (P < 0.05), and the acetate to propionate ratio (P < 0.01). The copy numbers of total bacteria (P < 0.05), Fibrobacter succinogenes (P < 0.01), Selenomonas ruminantium (P < 0.01), and Prevotella spp. (P < 0.05) in the FSBM group were greater, while the density of Prevotella ruminicola (P < 0.05) was lower than those in the SBM treatment. Additionally, Succiniclasticum ruminis and Saccharofermentans acetigenes were significantly enriched (P < 0.05) in the rumen fluid of FSBM-fed cows, despite the fact that there was no remarkable difference in the Alpha diversity indexes, structure and KEGG pathway abundances of the bacterial community across the two treatments. It could hence be concluded that the substitution of FSBM for SBM modulated rumen fermentation and rumen bacterial microbiota in lactating Holstein dairy cows. Further research is required to elucidate the relevant mechanisms of FSBM, and provide more insights into the application of FSBM in dairy cattle.